Pogo mad origami book 3 - Kumar, Ravi (BPI INDIA New Delhi, 2008)
"Pogo Mad Origami Book 3" invites readers into the creative world of origami with fun, engaging projects suitable for all skill levels. This book features a variety of unique designs and step-by-step instructions that encourage imagination and dexterity. Perfect for both beginners and experienced folders, it promotes hands-on learning and offers an enjoyable way to explore the art of paper folding. With vibrant illustrations and clear guidance, this volume is an ideal resource for anyone looking to enhance their origami skills.